MORTALITY PATTERN OF TURKEYS IN AN ORGANIZED POULTRY FARM - C. Pandian; A.V. Omprakash; R. Richard Churchil; M. Babu; D.Thyagarajan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was carried out in turkey birds maintained at Institute of Poultry Production and Management, TANUVAS, Chennai, spread over 3 years (2009-2010 to 2011-2012). Causative agents were listed and per cent mortality was calculated during different seasons. There are four seasons, viz. winter, summer, southwest monsoon and northeast monsoon. Brooder and grower turkey (0-20 weeks) and adult turkey (21-68 weeks) were reared in deep litter system of management. The overall mortality pattern during brooder and grower period (0-20 weeks) revealed that in southwest monsoon the mortality was the highest (53.81 %), followed by 22.39 % during summer, 17.93% in northeast monsoon and the lowest (5.86%) in winter. The overall mortality due to omphalitis was high (28.71%) and significantly (P<0.05) influenced by season. Colibacillosis, hepatitis and turkey pox incidences were also significantly (P<0.05) influenced by season and the overall per cent mortality incidences were 18.88, 17.23 and 5.81 respectively. Debility and non specific causes for mortality were 15.15 and 14.18 per cent respectively. The causes of mortality in layer turkey observed were hepatitis (40.56 %), Staphylococcal infection (18.56%), pneumonia (6.21%) and non specific (34.66%) in that order from high to low. The mortality during laying period due to hepatitis was higher during winter (67.30%) and southwest monsoon (46.96%). The incidences of pneumonia and Staphylococcal infections were observed only in monsoon.